True to the language game : African American discourse, cultural politics, and pedagogy - Gilyard, Keith (New York : Routledge, 2011)
In True to the Language Game, Keith Gilyard, one of the major African American figures to emerge in language and cultural studies, makes his most seminal work available in one volume. This collection of new and previously published essays contains Gilyard$1 (Bs most relevant scholarly contributions to deliberations about linguistic diversity, cultural identity, critical literacy, writing instruction, literary texts, and popular culture. The volume also features contemporary treatises on such timely topics as "students$1 (Bright to their own language," code-switching pedagogy, and political discourse surrounding the rise of Barack Obama. Gilyard weaves together serious analysis, theoretical work, policy discussions, and personal reflections on the interplay of language, literacy, and social justice to make True to the Language Game essential reading for students and scholars in rhetorical studies, composition studies, applied linguistics, and education.s
Includes bibliographical references and index.
Keywords: Language and education -- United States; Language and languages -- Political aspects; African Americans -- Education; Language and culture -- United States